Pengembangan Organisasi PMI Provinsi Gorontalo: Pendekatan Sistematis untuk Peningkatan Efisiensi Pengelolaan Stok Darah - Monoarfa, Valentina; Salade, Rafmi; Patilima, Ririn Andriani; Husain, Nur Hasana A.; Napi, Yunanda; Ngguyu, Revalina (MES Bogor, 2025)
Efficiency in blood stock management is a major challenge faced by the Indonesian Red Cross (PMI) in Gorontalo City due to increasing blood demand. This article examines the organizational development of PMI through a systematic approach by integrating SWOT analysis, the PDCA cycle, Fishbone diagram, and decision tree as tools to improve the effectiveness of blood stock management. Information technology plays a crucial role in supporting the transformation of work processes and enhancing data accuracy. This study is based on the theory of organizational development diagnosis and dialogic approach, emphasizing the active involvement of all members in the change process. Findings show that the combination of analytical methods and the utilization of technology can strengthen sustainable blood stock management. This approach is expected to serve as a strategic model for adaptive and responsive organizational development to the dynamics of community needs.